Characterization of Li1-xNi1+xO2prepared by the thermal-assisted precipitation process - Titipun Thongtem (2018)
Li1-xNi1+xO2was prepared by the thermal-assisted precipitation process of LiOH • H2O and Ni(CH3COO)2• 4H2O at a pH of 6-13 followed by the high temperature calcination for a variety of prolonged times. Phases, morphologies and constituents were characterized using an x-ray diffractometer (XRD), a scanning electron microscope (SEM), an energy dispersive x-ray (EDX) analyzer an atomic absorption spectrophotometer (AAS) and titration. Maximum [I(003)/I(104)] and minimum [I(006+102)/I(101)] intensity ratios were used to determine the preparation conditions. In addition, possible formation reactions of the precursors and calcined products were proposed. © 2008 MAIK Nauka.